Reproducibility and criterion validity of two radiographic techniques for variations in mandibular premolar compared with CBCT technique - Rincón Rodriguez, Martha Liliana; Martínez-Vega, Ruth Aralí; Duarte Monsalve , Martha Lucely; Moreno Monsalve, Jaime Omar (Revista Cuidarte, 2022)
Introduction: Considering that the existence of anatomical variations causes endodontic treatment failures, therefore it is important to diagnose them. This study aimed to determine the reproducibility and criterion validity of phosphor plate radiographs and sensor-based radiovisiography to identify anatomical variations detected by cone-beam computed tomography (CBCT) in lower premolars. Materials and Methods: 140 premolars images were obtained by CBCT, radiographs and radiovisiography. Independent interpretation was performed by two endodontists to evaluate the Vertucci classification and ramifications. Intraobserver and interobserver reproducibility were determined. Sensitivity, specificity and areas under the receiver-operator curve (AUC) were calculated using CBCT as the gold standard. Results: Intraobserver and interobserver reproducibility was higher for radiography. For Vertucci type I, radiography showed higher sensitivity (94.7%), specificity (64.9%) and AUC (0.795) than radiovisiography (89.3%, 62.2% and 0.757, respectively), similarly for type V (radiography at 69.2%, 93% and 0.8111; radiovisiography at 50%, 84.2% and 0.671, respectively). None of the techniques contributed to the diagnosis of type III (AUC < 0.5). Ramifications were infrequent (2.9%) with a low level of detection (sensitivity at 25% for radiography and 0% for radiovisiography). Discussion: This is the first study to evaluate the reproducibility and validity of these two radiographic techniques compared with CBCT for the detection of anatomical variations in teeth. Conclusions: Phosphor plate radiography showed higher reproducibility and validity for the diagnosis of Vertucci types I and V, which were the most frequent premolar variations found. This is a dissertation for the Master’s degree in Dentistry available in the repository of the Universidad Santo Tomas, Bucaramanga campus. How to cite this article: Rincón-Rodriguez Martha Liliana, Martínez-Vega Ruth Aralí, Duarte Martha Lucely, Moreno Monsalve Jaime Omar. Reproducibilidad y validez de criterio de dos técnicas radiográficas para variaciones de premolares mandibulares comparadas con CBCT. Revista Cuidarte. 2022;13(1):e2300. http://dx.doi.org/10.15649/cuidarte.2300